PENDIDIKAN DAN TRANSFORMASI SOSIAL TENTANG PANDANGAN SOSIOLOGI TERHADAP DINAMIKA MASYARAKAT - Nitaliya, Bella; kurnia, Ulfa isni; lathifah, Afra (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2025)
This article examines the relationship between education and transformation in the context of sociological views on societal dynamics. Education, as one of the social mediators, has an important role in shaping the social structure and norms that exist in society. Through a sociological approach, this article explains how education not only functions to transmit knowledge, but also to change the mindset, attitude and behavior of individuals in the face of social changes that continue to develop. This discussion includes relevant sociological theories, such as functionalism theories, conflicts, and symbolic interactionism, to understand how education can be a tool to reduce social inequality and facilitate social mobility. In addition, this article also discusses the opposition and opportunities faced by the education system in the face of social transformation influenced by globalization, technology, and cultural change. Overall, education plays a central role in the process of transforming society that is more inclusive and adaptive to the social dynamics that occur.